High-elasticity and high-viscosity composite modified emulsified asphalt for cold paving overlay construction and preparation method of high-elasticity and high-viscosity composite modified emulsified asphalt

By adding waste glue powder and SBR to the emulsified asphalt, a stable spatial network structure is formed, which solves the problem of insufficient high-temperature stability and bonding performance of emulsified asphalt, and improves the construction quality of the cold-laying cover layer and The durability of the road surface achieves low energy consumption and environmentally friendly construction.

CN119264692AActive Publication Date: 2025-01-07SHANBEI GUOLIN HIGHWAY MAINTENANCE ENG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411691796.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The high-temperature stability and bonding performance of emulsified asphalt in the cold-paved cover layer are insufficient, resulting in a decrease in construction quality and affecting the durability and service life of the road surface.

Method used

High elastic and high viscosity composite modified emulsified asphalt is used to add waste glue powder, SBR and petroleum resin as modifiers, combined with hydrogen peroxide treatment and ultrasonic impregnation technology to form a stable spatial network structure to improve dynamic viscosity and elasticity Restore performance.

Benefits of technology

It significantly improves the viscosity and elastic recovery performance of emulsified asphalt, enhances the bonding strength with aggregate, extends the durability and service life of the road surface, simplifies the construction process, and reduces energy consumption and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151150540000101
    Figure BDA0005151150540000101
  • Figure BDA0005151150540000111
    Figure BDA0005151150540000111
Patent Text Reader

Abstract

The invention relates to the field of asphalt materials, and particularly discloses high-elasticity and high-viscosity composite modified emulsified asphalt for cold paving overlay construction and a preparation method thereof, and the high-elasticity and high-viscosity composite modified emulsified asphalt comprises the following raw materials: matrix asphalt, 2-5 parts of an emulsifier, a stabilizer, a ductility enhancer, a pH regulator and a modifier; the modifier comprises a mixture of waste rubber powder, SBR (Styrene Butadiene Rubber) and petroleum resin; the preparation method comprises the following steps: heating the matrix asphalt, adding the modifier, heating, and shearing in a colloid mill to obtain an asphalt mixture; mixing an emulsifier, a stabilizer, a ductility enhancer, a pH regulator and water, heating, stirring and mixing to obtain liquid soap; mixing the asphalt mixture and the soap liquid, feeding the mixture into a colloid mill for shearing and emulsifying, and then cooling to obtain the high-viscosity high-elasticity composite modified emulsified asphalt. The preparation method has the characteristics that the quality of the emulsified asphalt evaporation residues, especially the dynamic viscosity and the elastic recovery quality, is improved, and the high-elasticity and high-viscosity modified emulsified asphalt is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt materials, and more specifically, to a high-elasticity and high-viscosity composite modified emulsified asphalt used for cold-laid overlay construction and a preparation method thereof. Background Art

[0002] At present, in road engineering, in order to improve the durability and performance of the road surface, various types of asphalt materials are widely used in different layers on the road surface. Although traditional hot-mix asphalt mixtures have good compaction performance and strength, they consume a lot of energy during production and construction, and have a great impact on the environment. Therefore, in recent years, cold-laid asphalt has received more and more attention as an energy-saving and environmentally friendly alternative material.

[0003] At present, the common cold-laid asphalt materials on the market are mainly emulsified asphalt. Emulsified asphalt is made by heat melting and mechanical action, and dispersed in water containing emulsifiers and stabilizers in a droplet state to form an oil-in-water or oil-in-water emulsion. It is mainly used for road surface treatment, bonding layer, permeable layer, sealing layer, etc. to improve the durability and stability of the road. Emulsified asphalt does not need to be heated during use, and the stone does not need to be heated. It has many advantages such as simple construction, low cost, low carbon and energy saving. Overlay refers to a thin asphalt surface layer of fine stones laid on the original asphalt pavement to improve the quality of asphalt pavement, improve the waterproof, anti-skid ability and flatness of the pavement. With the continuous increase in traffic volume and the increasingly serious problem of road aging, cold-laid overlay will be more widely used as a fast, efficient and environmentally friendly road maintenance method.

[0004] The application of emulsified asphalt in cold-laid overlay can avoid the tedious process of high-temperature heating and stirring of hot-mix asphalt, thereby simplifying the construction process and improving construction efficiency. As one of the main materials for cold-laid overlay, the performance quality of emulsified asphalt directly affects the construction quality of the cold-laid overlay.

[0005] Due to the effects of emulsified asphalt emulsifiers and mechanical stirring, the high-temperature stability, adhesion, deformation resistance and deformation recovery properties of the current emulsified asphalt have been reduced, which directly affects the combination of emulsified asphalt with aggregates when used in cold-laid overlays, affecting the construction quality. For example, segregation and stratification may occur during the construction process. Its elastic recovery performance will affect the deformation of the subsequent cold-laid overlay under vehicle loads, affecting the durability and service life of the road surface.

[0006] Therefore, in order to ensure the quality of overlay asphalt, the emulsified asphalt needs to be modified to improve the quality of its emulsified asphalt evaporation residue, especially the dynamic viscosity and elastic recovery quality. The above properties directly affect the high-temperature stability and elasticity of the emulsified asphalt, and thus affect the final bonding strength and anti-degradation performance with the aggregate. Summary of the invention

[0007] In order to improve the quality of the evaporation residue of emulsified asphalt, especially the dynamic viscosity and elastic recovery quality, and to obtain highly elastic and highly viscous modified emulsified asphalt, the present application provides a highly elastic and highly viscous composite modified emulsified asphalt for cold-laid overlay construction and a preparation method thereof.

[0008] In the first aspect, the present application provides a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction, which adopts the following technical solution: A high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction, comprising the following raw materials in parts by weight: 70-85 parts of base asphalt, 2-5 parts of emulsifier, 0.2-0.5 parts of stabilizer, 5-10 parts of extender, 1-3 parts of pH regulator and 6-13 parts of modifier; The modifier comprises a mixture of waste rubber powder, SBR and petroleum resin in a mass ratio of 1: (0.5-0.8): (0.2-0.4).

[0009] By adopting the above technical scheme, the modifier in this application is added with waste rubber powder, SBR and petroleum resin. SBR (styrene-butadiene rubber) as a rubber modifier can enhance the viscosity and elasticity of asphalt, and petroleum resin as a resin modifier can improve the adhesion of base asphalt. In this application, part of the waste rubber powder is used to replace SBR as a modifier for emulsified asphalt. When the waste rubber powder is mixed with the base asphalt, the two have a larger bonding area and stronger molecular force, thereby improving the dynamic viscosity of the emulsified asphalt through physical mixing, and in the preparation process of the modified emulsified asphalt, Under the action of high temperature and mechanical force, the desulfurization reaction of waste rubber powder causes the macromolecules of waste rubber powder to break, and the newly generated small molecular chains dissolve in the asphalt to form a stable spatial network structure, thus achieving the purpose of modification. In addition, the waste rubber powder can also absorb the light oil in the matrix asphalt and undergo a swelling reaction, thereby increasing the viscosity of the emulsified asphalt, making it easier to adhere to aggregates and improving the durability of the road surface. In addition, due to the addition and swelling effect of waste rubber powder, the modified emulsified asphalt also has better elastic recovery properties. The final emulsified asphalt has high viscosity and high elasticity, which significantly improves the performance of the emulsified asphalt.

[0010] Optionally, the waste rubber powder is added after being modified by the following method: After the waste rubber powder is crushed, it is first immersed in a hydrogen peroxide solution for drying to obtain pretreated waste rubber powder; Then the pretreated waste rubber powder is subjected to pressure immersion treatment in a mixed modification liquid of tert-butyl vinyl carbonate, ruthenium tetroxide, initiator, organic bentonite and water, and then washed with water and dried to obtain the modified waste rubber powder.

[0011] By adopting the above technical scheme, since the surface energy of the waste rubber powder particles is relatively high and the molecular structure thereof is quite different from that of the matrix asphalt, the waste rubber powder particles are prone to agglomeration and precipitation in the matrix asphalt. Therefore, in the present application, the waste rubber powder is treated with a hydrogen peroxide oxidizing agent to break some of the chemical bonds on its surface, which can effectively reduce the molecular weight of the waste rubber powder, and introduce carbonyl and carboxyl groups into the waste rubber powder, which is then subjected to pressure immersion treatment in a mixed modified liquid. Under the action of a ruthenium tetroxide catalyst, more carboxyl groups are introduced into the surface of the waste rubber powder, and then a small molecule anti-settling agent organic bentonite is introduced into the surface of the waste rubber powder through the hydroxyl groups on the organic bentonite, and then the action of tert-butyl vinyl carbonate is combined with the double bond in the waste rubber powder under the action of an initiator, thereby introducing tert-butyl vinyl carbonate groups, and utilizing its steric hindrance effect to further prevent the agglomeration of the waste rubber powder particles, thereby facilitating the mixed dispersion of the modified waste rubber powder in the matrix asphalt, and further improving the viscosity and elasticity of the modified emulsified asphalt.

[0012] Optionally, during the preparation of the modified waste rubber powder, the amount of hydrogen peroxide solution added is 5-8 times the mass of the waste rubber powder, and the mass concentration of the hydrogen peroxide solution is 15-30wt%; The amount of the mixed modified liquid added is 3-5 times the mass of the pretreated waste rubber powder, and the mixed modified liquid is prepared by mixing 8-12 parts by weight of versatate vinyl carbonate, 1-3 parts by weight of ruthenium tetroxide, 0.5-1.5 parts by weight of initiator, 5-10 parts by weight of organic bentonite and 20-30 parts by weight of water.

[0013] By adopting the above technical scheme and controlling the amount of raw material added, the dispersion uniformity of the modified asphalt prepared by mixing the modified waste rubber powder with the base asphalt is better, and the dynamic viscosity and elastic recovery performance of the modified emulsified asphalt are better.

[0014] Optionally, when the waste rubber powder is modified, the mixed modified liquid is pressurized and impregnated under the following conditions: the impregnation pressure is 2.5-4MPa, the impregnation temperature is 55-65°C, and the impregnation time is 90-150min.

[0015] By adopting the above technical solution, when the pretreated waste rubber powder is immersed in the above mixed modifying liquid under pressure, the modification effect is better.

[0016] Optionally, 5-8 parts by weight of p-hydroxybenzoic acid are also added to the mixed modified liquid.

[0017] By adopting the above-mentioned technical scheme, p-hydroxybenzoic acid is added to the mixed modified liquid in the present application. The hydroxyl group of p-hydroxybenzoic acid reacts with the activated carboxyl group on the waste rubber powder, thereby introducing a small molecule benzene ring structure on the waste rubber powder. The benzene ring structure has a high affinity for aromatic hydrocarbons, which can not only improve the compatibility with the matrix asphalt, but also enhance the interaction between the matrix asphalt and SBR, so that the composite modifier of the modified waste rubber powder and SBR is dispersed in the matrix asphalt in the form of a spatial network, thereby greatly improving the performance of the emulsified asphalt.

[0018] Optionally, the modified waste rubber powder is added after being loaded on the polyamide aerogel, and the specific operation is as follows: After the modified waste rubber powder is mixed with water, polyamide aerogel and polyvinyl alcohol are added, and the mixture is immersed in ultrasonic conditions for 20-30 minutes and then dried.

[0019] By adopting the above technical scheme, in the present application, the modified waste rubber powder is loaded on the polyamide aerogel and then added as an additive. Under ultrasonic dispersion conditions, the modified waste rubber powder is filled and loaded on the surface of the polyamide aerogel and in the pore structure. Then, the viscosity of polyvinyl alcohol and the carboxyl groups on the modified waste rubber powder are used to form chemical bonds with the polyamide aerogel to improve the bonding strength between the modified waste rubber powder and the polyamide aerogel, prevent it from falling off, and achieve a more solid loading effect of the modified waste rubber powder on the polyamide aerogel. The elasticity of the polyamide aerogel is used to improve the elastic recovery performance and dynamic viscosity of the modified emulsified asphalt. In addition, the similarity in chemical structure and good interaction force between the polyamide aerogel and the asphalt matrix make the polyamide aerogel more compatible with the asphalt matrix than the waste rubber powder, so that the polyamide aerogel, as a carrier of the waste rubber powder, can further improve the dispersibility and stability of the waste rubber powder. At the same time, it can also absorb and store the light components in the asphalt through its porous structure, further improve the performance of the asphalt, and finally obtain a modified emulsified asphalt with better comprehensive performance.

[0020] Optionally, when the modified waste rubber powder is loaded on the polyamide aerogel, the mass ratio of the modified waste rubber powder to water is 1:(5-7), the mass ratio of the polyamide aerogel to the modified waste rubber powder is 1:(0.4-0.6), and the amount of polyvinyl alcohol added is 3-5wt% of the amount of modified waste rubber powder added.

[0021] Optionally, the stabilizer is a mixture of calcium chloride, microcrystalline wax and WSG-104H emulsified asphalt stabilizer in a mass ratio of 1:(0.2-0.3):(2-3).

[0022] By adopting the above technical scheme, the stabilizer in this application is selected on the basis of traditional calcium chloride inorganic salt and WSG-104H emulsified asphalt stabilizer. The WSG-104H emulsified asphalt stabilizer effectively solves the problems of long-term storage precipitation of emulsified asphalt, poor emulsification effect, crusting and demulsification, and significantly improves the quality of emulsified asphalt. The addition of a small amount of microcrystalline wax can form a protective film in the emulsified asphalt to prevent the aggregation and stratification of asphalt particles, thereby improving the stability of the emulsified asphalt. Moreover, the addition of microcrystalline wax can form a tiny elastic network structure in the asphalt, thereby improving the elastic recovery ability of the asphalt, which helps to improve the modified emulsified asphalt road. When subjected to external forces such as vehicle loads, it can better maintain its flatness and durability, and its small addition prevents its asphalt viscosity from decreasing too much.

[0023] Optionally, the emulsifier is a cationic emulsifier, and the pH adjuster is phosphoric acid.

[0024] Optionally, the retardant is a mixture of mineral oil and polyethylene wax in a mass ratio of 1:(0.3-0.5).

[0025] By adopting the above technical solution, oily substances can improve the ductility of emulsified asphalt by improving the fluidity and elasticity of asphalt. The addition of polyethylene wax can significantly reduce the penetration of asphalt while increasing the softening point and ductility of asphalt. When too much polyethylene wax is added, its ductility is reduced. When the amount added in this application is selected, the overall performance of the final emulsified asphalt is better.

[0026] In a second aspect, the present application provides a method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction, using the following technical solution: A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction comprises the following steps: S1. Firstly, heat the base asphalt to 170-180°C, then add the modifier, heat to 180-190°C and stir, then put it into the colloid mill for shearing to obtain an asphalt mixture; S2, mixing the emulsifier, stabilizer, extending agent, pH adjuster and water, heating to 70-80° C., and stirring to obtain a soap solution; S3, mixing the asphalt mixture obtained in step S1 with the soap solution in step S2 and simultaneously entering into a colloid mill for shear emulsification, and then cooling to obtain a high-viscosity and high-elasticity composite modified emulsified asphalt.

[0027] By adopting the above technical scheme, the method provided by the present application is simple and convenient, and is easy to realize industrialization. In the present application, the modifier and the base asphalt are first dispersed and then mixed with the soap solution for shear emulsification. How to make the mixing dispersion of the waste rubber powder in the modifier and the base asphalt better, so as to better improve the performance of the final emulsified asphalt.

[0028] In summary, this application has the following beneficial effects: 1. The modifier in the present application is added with waste rubber powder, SBR and petroleum resin. In the present application, part of the waste rubber powder is used to replace SBR as the modifier of emulsified asphalt. When the waste rubber powder is mixed with the base asphalt, the two have a large bonding area and a strong molecular force, thereby improving the dynamic viscosity of the emulsified asphalt through physical mixing. In addition, during the preparation process of the modified emulsified asphalt, under the action of high temperature and mechanical force, the desulfurization reaction of the waste rubber powder causes the macromolecules of the waste rubber powder to break, and the newly generated small molecular chains are dissolved in the asphalt to form a stable spatial network structure, thereby achieving the purpose of modification. In addition, the waste rubber powder can also absorb the light oil in the base asphalt and undergo a swelling reaction, thereby increasing the viscosity of the emulsified asphalt, making it easier to adhere to aggregates and improving the durability of the road surface. In addition, due to the addition and swelling of the waste rubber powder, the modified emulsified asphalt also has better elastic recovery performance. The finally prepared emulsified asphalt has high viscosity and high elasticity, and the performance of the emulsified asphalt is significantly improved. 2. In the present application, hydrogen peroxide is used to oxidize the waste rubber powder to break some of the chemical bonds on its surface, which can effectively reduce the molecular weight of the waste rubber powder, and introduce carbonyl and carboxyl groups on the waste rubber powder, and then the waste rubber powder is subjected to pressure immersion treatment in a mixed modified liquid. Under the action of a ruthenium tetroxide catalyst, more carboxyl groups are introduced on the surface of the waste rubber powder, and then a small molecule anti-settling agent organic bentonite is introduced on the surface of the waste rubber powder through the hydroxyl groups on the organic bentonite, and then with the action of tert-butyl vinyl carbonate, tert-butyl vinyl carbonate is double-bonded with the waste rubber powder under the action of an initiator, thereby introducing tert-butyl carbonate groups, and utilizing its steric hindrance effect to further prevent the agglomeration of waste rubber powder particles, thereby facilitating the mixed dispersion of the modified waste rubber powder in the matrix asphalt, and further improving the viscosity and elasticity of the modified emulsified asphalt; 3. In the present application, p-hydroxybenzoic acid is added to the mixed modified liquid. The hydroxyl group of p-hydroxybenzoic acid reacts with the activated carboxyl group on the waste rubber powder, thereby introducing a small molecule benzene ring structure on the waste rubber powder. The benzene ring structure has a high affinity for aromatic hydrocarbons, which can not only improve the compatibility with the matrix asphalt, but also enhance the interaction between the matrix asphalt and SBR, so that the composite modifier of the modified waste rubber powder and SBR is dispersed in the matrix asphalt in the form of a spatial network, thereby greatly improving the performance of the emulsified asphalt; 4. In the present application, the modified waste rubber powder is loaded on the polyamide aerogel and then added as an additive. Under ultrasonic dispersion conditions, the modified waste rubber powder is filled and loaded on the surface and pore structure of the polyamide aerogel. Then, the viscosity of polyvinyl alcohol and the carboxyl groups on the modified waste rubber powder are used to form chemical bonds with the polyamide aerogel to improve the bonding strength between the modified waste rubber powder and the polyamide aerogel, prevent it from falling off, and achieve a more solid loading effect of the modified waste rubber powder on the polyamide aerogel. The elasticity of the polyamide aerogel is used to improve the elastic recovery performance and dynamic viscosity of the modified emulsified asphalt. In addition, the similarity in chemical structure and good interaction force between the polyamide aerogel and the asphalt matrix make the polyamide aerogel more compatible with the asphalt matrix than the waste rubber powder. Therefore, the polyamide aerogel can be used as a carrier of waste rubber powder to further improve the dispersibility and stability of the waste rubber powder. At the same time, it can also absorb and store light components in the asphalt through its porous structure, further improve the performance of the asphalt, and finally obtain a modified emulsified asphalt with better comprehensive performance. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0030] In the following examples, the base asphalt is AH-70 heavy road asphalt; The petroleum resin is C9 petroleum resin; the WSG-104H emulsified asphalt stabilizer is the WSG-104H emulsified asphalt stabilizer produced by Shanghai Wanzhao Fine Chemical Co., Ltd.; The mineral oil is 55# white oil; the SBR is styrene-butadiene latex model SBRL-65 produced by Xinxiang Longteng Highway Technology Co., Ltd.

[0031] The polyamide aerogel is a polyamide elastomer-based aerogel, which is formed by combining a polyamide elastomer with an aerogel. The aerogel can be commercially available or customized. In the following embodiments, the polyamide aerogel is prepared by the following method: Take a polyamide elastomer and propanol in a mass ratio of 1:5, mix them, heat to 90°C and stir for 7 hours after ultrasonic dispersion to dissolve the mixed solution, then pour the mixed solution into a beaker, place the beaker in a dry ice-ethanol mixture for freezing at -30°C and for 3 hours to obtain a solid mixture, then evacuate the solid mixture in a freeze dryer and freeze-dry it at -100°C for 80 hours to obtain a polyamide elastomer-based aerogel.

[0032] Example 1 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction comprises the following steps: S1. First, heat 75g of base asphalt to 175°C, then add 10g of modifier, heat to 185°C and stir, then put into colloid mill for shearing, the speed of colloid mill is 5500r / min, to obtain asphalt mixture; The modifier is obtained by mixing waste rubber powder, SBR and C9 petroleum resin in a mass ratio of 1:0.6:0.3; S2, 3 g of emulsifier, 0.3 g of stabilizer, 8 g of extender, 2 g of pH regulator and 62 g of water were mixed, heated to 75° C., and stirred to obtain a soap solution; Among them, the emulsifier is octadecyl trimethyl ammonium chloride cationic emulsifier, the pH regulator is phosphoric acid, the extender is a mixture of mineral oil and polyethylene wax in a mass ratio of 1:0.4, and the stabilizer is a mixture of calcium chloride, microcrystalline wax and WSG-104H emulsified asphalt stabilizer in a mass ratio of 1:0.2:2.5. S3. The asphalt mixture obtained in step S1 is mixed with the soap solution in step S2 and then simultaneously enters a colloid mill for shear emulsification. The rotation speed of the colloid mill is 3800 r / min. After cooling, a high-viscosity and high-elasticity composite modified emulsified asphalt is obtained.

[0033] Example 2 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction comprises the following steps: S1. First, heat 70g of base asphalt to 170°C, then add 6g of modifier, heat to 180°C and stir, then put into a colloid mill for shearing, the speed of the colloid mill is 5000r / min, to obtain an asphalt mixture; The modifier is obtained by mixing waste rubber powder, SBR and C9 petroleum resin in a mass ratio of 1:0.5:0.2; S2, 2 g of emulsifier, 0.2 g of stabilizer, 5 g of extender, 1 g of pH regulator and 55 g of water were mixed, heated to 70° C., and stirred to obtain a soap solution; Among them, the emulsifier is octadecyl trimethyl ammonium chloride cationic emulsifier, the pH regulator is phosphoric acid, the extender is a mixture of mineral oil and polyethylene wax in a mass ratio of 1:0.3, and the stabilizer is a mixture of calcium chloride, microcrystalline wax and WSG-104H emulsified asphalt stabilizer in a mass ratio of 1:0.2:2. S3. The asphalt mixture obtained in step S1 is mixed with the soap solution in step S2 and then simultaneously enters a colloid mill for shear emulsification. The rotation speed of the colloid mill is 3500 r / min. After cooling, a high-viscosity and high-elasticity composite modified emulsified asphalt is obtained.

[0034] Example 3 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction comprises the following steps: S1. 85g of base asphalt was first heated to 180°C, then 13g of modifier was added, the temperature was raised to 190°C and stirred, and then the mixture was put into a colloid mill for shearing at a rotation speed of 6000r / min to obtain an asphalt mixture; The modifier is obtained by mixing waste rubber powder, SBR and C9 petroleum resin in a mass ratio of 1:0.8:0.4; S2, 5 g of emulsifier, 0.5 g of stabilizer, 10 g of extender, 3 g of pH regulator and 70 g of water were mixed, heated to 80° C., and stirred to obtain a soap solution; Among them, the emulsifier is octadecyl trimethyl ammonium chloride cationic emulsifier, the pH regulator is phosphoric acid, the extender is a mixture of mineral oil and polyethylene wax in a mass ratio of 1:0.5, and the stabilizer is a mixture of calcium chloride, microcrystalline wax and WSG-104H emulsified asphalt stabilizer in a mass ratio of 1:0.3:3; S3. The asphalt mixture obtained in step S1 is mixed with the soap solution in step S2 and then simultaneously enters a colloid mill for shear emulsification. The rotation speed of the colloid mill is 4000 r / min. After cooling, a high-viscosity and high-elastic composite modified emulsified asphalt is obtained.

[0035] Example 4 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that the waste rubber powder in the modifier in step S1 is modified by the following method and then added: The waste rubber powder is crushed and then immersed in a hydrogen peroxide solution for drying to obtain pretreated waste rubber powder, wherein the amount of hydrogen peroxide solution added is 6 times the mass of the waste rubber powder, and the mass concentration of the hydrogen peroxide solution is 20wt%; The pretreated waste rubber powder is then impregnated under pressure in a mixed modification solution of tert-butyl vinyl carbonate, ruthenium tetroxide, initiator, organic bentonite and water. The impregnation pressure is 3 MPa, the impregnation temperature is 60°C, the impregnation time is 120 min, and then washed with water and dried to obtain the modified waste rubber powder.

[0036] The amount of the mixed modified liquid added is 4 times the mass of the pretreated waste rubber powder, and the mixed modified liquid is used as a benchmark. The mixed modified liquid is prepared by mixing 10g of versatate, 2g of ruthenium tetroxide, 1g of initiator potassium persulfate, 8g of organic bentonite and 25g of water.

[0037] Example 5 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that the waste rubber powder in the modifier in step S1 is modified by the following method and then added: The waste rubber powder is crushed and then immersed in a hydrogen peroxide solution for drying to obtain pretreated waste rubber powder, wherein the amount of hydrogen peroxide solution added is 5 times the mass of the waste rubber powder, and the mass concentration of the hydrogen peroxide solution is 15wt%; The pretreated waste rubber powder is then impregnated under pressure in a mixed modification solution of tert-butyl vinyl carbonate, ruthenium tetroxide, initiator, organic bentonite and water. The impregnation pressure is 2.5 MPa, the impregnation temperature is 55°C, the impregnation time is 150 min, and then washed with water and dried to obtain the modified waste rubber powder.

[0038] The amount of the mixed modified liquid added is 3 times the mass of the pretreated waste rubber powder, and the mixed modified liquid is used as a benchmark. The mixed modified liquid is prepared by mixing 8g of versatate, 1g of ruthenium tetroxide, 0.5g of initiator potassium persulfate, 5g of organic bentonite and 20g of water.

[0039] Example 6 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that the waste rubber powder in the modifier in step S1 is modified by the following method and then added: The waste rubber powder is crushed and then immersed in a hydrogen peroxide solution for drying to obtain pretreated waste rubber powder, wherein the amount of hydrogen peroxide solution added is 8 times the mass of the waste rubber powder, and the mass concentration of the hydrogen peroxide solution is 30wt%; The pretreated waste rubber powder is then impregnated under pressure in a mixed modification solution of tert-butyl vinyl carbonate, ruthenium tetroxide, initiator, organic bentonite and water. The impregnation pressure is 4 MPa, the impregnation temperature is 65°C, the impregnation time is 90 min, and then washed with water and dried to obtain the modified waste rubber powder.

[0040] The amount of the mixed modified liquid added is 3-5 times the mass of the pretreated waste rubber powder, and the mixed modified liquid is used as a benchmark. The mixed modified liquid is prepared by mixing 12g of versatate, 3g of ruthenium tetroxide, 1.5g of initiator potassium persulfate, 10g of organic bentonite and 30g of water.

[0041] Example 7 A method for preparing a high-elasticity and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 4, except that no versatate is added to the mixed modified liquid.

[0042] Example 8 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 4, except that 5g of p-hydroxybenzoic acid is also added to the mixed modified liquid.

[0043] Example 9 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 4, except that 8g of p-hydroxybenzoic acid is also added to the mixed modified liquid.

[0044] Example 10 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 4, except that the prepared modified waste rubber powder is loaded on the polyamide aerogel and then added. The specific operation is: After the modified waste rubber powder and water were mixed in a mass ratio of 1:6, polyamide aerogel and polyvinyl alcohol were added, the mass ratio of polyamide aerogel to modified waste rubber powder was 1:0.5, the amount of polyvinyl alcohol added was 4wt% of the amount of modified waste rubber powder added, and the mixture was immersed under ultrasonic conditions for 25 minutes and then dried.

[0045] Embodiment 11 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 4, except that the prepared modified waste rubber powder is loaded on the polyamide aerogel and then added. The specific operation is: After the modified waste rubber powder and water were mixed in a mass ratio of 1:5, polyamide aerogel and polyvinyl alcohol were added, the mass ratio of polyamide aerogel to modified waste rubber powder was 1:0.4, the amount of polyvinyl alcohol added was 3wt% of the amount of modified waste rubber powder added, and the mixture was immersed under ultrasonic conditions for 20 minutes and then dried.

[0046] Example 12 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 4, except that the prepared modified waste rubber powder is loaded on the polyamide aerogel and then added. The specific operation is: After the modified waste rubber powder and water were mixed in a mass ratio of 1:7, polyamide aerogel and polyvinyl alcohol were added, the mass ratio of polyamide aerogel to modified waste rubber powder was 1:0.6, the amount of polyvinyl alcohol added was 5wt% of the amount of modified waste rubber powder added, and the mixture was immersed under ultrasonic conditions for 30 minutes and then dried.

[0047] Comparative Example 1 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that no modifier is added to the raw materials.

[0048] Comparative Example 2 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that the modifier is waste rubber powder.

[0049] Comparative Example 3 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that an equal amount of SBR in the modifier is replaced by SBS.

[0050] Comparative Example 4 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that no microcrystalline wax is added to the stabilizer.

[0051] Comparative Example 5 A method for preparing a high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction is carried out according to the method in Example 1, except that an equal amount of microcrystalline wax in the stabilizer is replaced by paraffin.

[0052] Performance Testing First, referring to T0620, the 60°C dynamic viscosity and elastic recovery (25°C) properties of the evaporation residue of the modified emulsified asphalt obtained in the examples and comparative examples of the present application were tested, and the test results are shown in Table 1 below.

[0053] Table 1: Referring to the test results in Table 1 above, the modified emulsified asphalt prepared in the examples of the present application has excellent 60°C dynamic viscosity and elastic recovery performance. The 60°C dynamic viscosity reflects the fluidity and stability of the emulsified asphalt under high temperature conditions and the bonding strength with the aggregate, while the elastic recovery property reflects the ability of the emulsified asphalt to return to its original shape after being subjected to force, which directly characterizes that it can quickly return to its original shape after being subjected to vehicle loads, thereby reducing permanent deformation of the road surface.

[0054] Referring to the test results of Examples 1 and 4-6 of the present application, it can be seen that after the waste rubber powder is modified, the dynamic viscosity and elasticity of the emulsified asphalt obtained are significantly improved. Combined with the test results of Example 7, when no tert-butyl vinyl carbonate is added to the mixed modifier, it affects the dispersion and distribution of the waste rubber powder in the matrix asphalt, thereby reducing the performance of the final emulsified asphalt; combined with the test results of Examples 8-9, when p-hydroxybenzoic acid is also added to the mixed modifier, its performance is further improved. Combined with the test results of Examples 10-12, when the waste rubber powder is loaded on the polyamide aerogel and added, its performance is significantly improved.

[0055] Combined with the test results of Example 1 and Comparative Example 1, when no modifier is added to the raw material, its dynamic viscosity and elastic recovery properties are significantly reduced, and when the modifier in Comparative Example 2 is directly replaced by waste rubber powder, its elastic recovery performance is significantly reduced. Although the dynamic viscosity is improved compared with Comparative Example 1, it is still much lower than that of Example 1. Combined with the test results of Comparative Example 3, when SBS and waste rubber powder are compounded as the modifier, its elastic recovery performance is much lower than that of Example 1. Combined with the test results in Examples 4 and 5, when microcrystalline wax is not added to the stabilizer or is replaced by paraffin, its elastic recovery performance is also reduced. When microcrystalline wax is compounded with traditional stabilizers, the performance of the final modified emulsified asphalt is better.

[0056] In addition, the modified emulsified asphalt prepared in Example 4 of the present application was subjected to the tests shown in Table 2 below, and the test results are shown in Table 2 below.

[0057] Table 2: Referring to the test results in Table 2 above, the performance of the modified emulsified asphalt prepared in the present application meets the requirements, and the modified emulsified asphalt prepared in the present application is used for cold-laid overlay construction, and no milling of the original road surface is required. It is widely used in corrective maintenance of highways, urban expressways and highways of all grades, and can quickly improve road conditions. It can also be used for preventive maintenance, and there is no smoke emission during construction at room temperature. The energy consumption is reduced by 80% compared with hot-mixed ultra-thin overlays, and the carbon dioxide emissions per ton of mixture are reduced by 2.5 kg and sulfur dioxide emissions are reduced by 0.3 kg.

[0058] Moreover, the modified emulsified asphalt prepared in this application is used in the modified super-strong overlay asphalt mixture, and its wet wheel abrasion test shows that the test value is 0g / m 2 , far exceeding the required value ≤540g / m 2 , 25℃ immersion in water for 6 days test value is 174.6g / m 2 , far exceeding the required value ≤800g / m 2 , the asphalt pavement construction has excellent resistance to water damage.

[0059] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction, characterized in that: It includes the following raw materials in parts by weight: 70-85 parts of base asphalt, 2-5 parts of emulsifier, 0.2-0.5 parts of stabilizer, 5-10 parts of extender, 1-3 parts of pH regulator and 6-13 parts of modifier; The modifier includes a mixture of waste rubber powder, SBR and petroleum resin in a mass ratio of 1: (0.5-0.8): (0.2-0.4).

2. The high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 1, characterized in that: The waste rubber powder is modified and added by the following method: After the waste rubber powder is crushed, it is first immersed in a hydrogen peroxide solution for drying to obtain pretreated waste rubber powder; Then the pretreated waste rubber powder is subjected to pressure immersion treatment in a mixed modification liquid of tert-butyl vinyl carbonate, ruthenium tetroxide, initiator, organic bentonite and water, and then washed with water and dried to obtain the modified waste rubber powder.

3. The high-elasticity and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 2, characterized in that: During the preparation of the modified waste rubber powder, the amount of hydrogen peroxide solution added is 5-8 times the mass of the waste rubber powder, and the mass concentration of the hydrogen peroxide solution is 15-30wt%; The amount of the mixed modified liquid added is 3-5 times the mass of the pretreated waste rubber powder, and the mixed modified liquid is prepared by mixing 8-12 parts by weight of versatate vinyl carbonate, 1-3 parts by weight of ruthenium tetroxide, 0.5-1.5 parts by weight of initiator, 5-10 parts by weight of organic bentonite and 20-30 parts by weight of water.

4. The high-elasticity and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 2, characterized in that: When the waste rubber powder is modified, the conditions for pressurized impregnation of the mixed modified liquid are: impregnation pressure is 2.5-4MPa, impregnation temperature is 55-65℃, and impregnation time is 90-150min.

5. The high-elasticity and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 3, characterized in that: 5-8 parts by weight of p-hydroxybenzoic acid are also added to the mixed modified liquid.

6. The high-elasticity and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 2, characterized in that: The modified waste rubber powder is loaded on the polyamide aerogel and then added, and the specific operation is as follows: After the modified waste rubber powder is mixed with water, polyamide aerogel and polyvinyl alcohol are added, and the mixture is immersed in ultrasonic conditions for 20-30 minutes and then dried.

7. The high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 6, characterized in that: When the modified waste rubber powder is loaded on the polyamide aerogel, the mass ratio of the modified waste rubber powder to water is 1:(5-7), the mass ratio of the polyamide aerogel to the modified waste rubber powder is 1:(0.4-0.6), and the amount of polyvinyl alcohol added is 3-5wt% of the amount of the modified waste rubber powder added.

8. The high-elasticity and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 1, characterized in that: The stabilizer is a mixture of calcium chloride, microcrystalline wax and WSG-104H emulsified asphalt stabilizer in a mass ratio of 1: (0.2-0.3): (2-3).

9. The high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to claim 1, characterized in that: The emulsifier is a cationic emulsifier, and the pH adjuster is phosphoric acid; The retardant is a mixture of mineral oil and polyethylene wax in a mass ratio of 1: (0.3-0.5).

10. The method for preparing the high-elastic and high-viscosity composite modified emulsified asphalt for cold-laid overlay construction according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Firstly, heat the base asphalt to 170-180°C, then add the modifier, heat to 180-190°C and stir, then put it into the colloid mill for shearing to obtain an asphalt mixture; S2, mixing the emulsifier, stabilizer, extending agent, pH adjuster and water, heating to 70-80° C., and stirring to obtain a soap solution; S3, mixing the asphalt mixture obtained in step S1 with the soap solution in step S2 and simultaneously entering into a colloid mill for shear emulsification, and then cooling to obtain a high-viscosity and high-elasticity composite modified emulsified asphalt.

Citation Information

Patent Citations

  • High-concentration colorful emulsified asphalt and preparation method thereof

    CN104356588A

  • High-strength emulsified asphalt and preparation method thereof

    CN110804318A

  • Preparation method of wheel-sticking-free emulsified asphalt for adhesive layer

    CN111777770A

  • Colored emulsified asphalt suitable for cold regions and preparation method thereof

    CN111925660A